Integrated Urban Water Resources Management - Hlavinek, Petr; Kukharchyk, Tamara; Marsalek, Jiri; Mahrikova, Ivana (Nato Security through Science Series C:, Environmental Security,, 2006)
Growing populations and rising standards of living exert stress on water supply and the quality of drinking water. In wastewater management, new challenges are caused by new chemicals of concern, including endocrine disrupters, pharmaceuticals, hormones, and personal care products, which often pass through wastewater treatment plants unabated, but may cause serious impacts on receiving aquatic ecosystems. Advanced wastewater treatment leads to production of biosolids, which are processed in various ways, including on-land applications in agriculture. Municipal effluents, combined with increasing withdrawals of water, lead to the worsening of receiving water quality. Expert opinions indicate that the only way to deal with the current urban water management dilemmas is by integrated management and innovative delivery of water services. This book presents important aspects of Challenges in Management of Urban Water Resources, Challenges in Urban Water Supply, Urban Drainage and Water Bodies, Wastewater Treatment and Security, and Wastewater Treatment and Reuse.